ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT MAHASISWA MELAKUKAN TINDAKAN WHISTLEBLOWING: STUDI PADA MAHASISWA AKUNTANSI STIE ASIA MALANG - Handika, Mellisa Fitri Dwi; Sudaryanti, Dwiyani (LP2M Institut Teknologi dan Bisnis Asia Malang, 2017)
Those are a lot of fraud that make the state agencies urge the accountans to report the fraud they knew. Whistleblowing is an effective way to detect any fraud. This study aims to examine the factors influencing whistleblowing intention, with Theory of Planned Behavior as a theoritical basis. Research data are collected by distributing questionnaires to 171 respondents. Hypothesis testing was analyzed by using multiple linear regressions. The results showed that attitude has no significant influence to whistleblowing intention, while subjective norm and perceived behavioral control has positively significant influence to whisleblowing intention. Simultantly attitude, subjective norm, and perceived behavioral control has significantly influence to whistleblowing intention. The results also showed the urgency of ethical aspect in curriculum and learning syste and the importance of ethical attitude and positive educative environment.